Ethnomedical Plants are used by Tribal Women in the Nuapada District to Treat Menstrual Problems - Gardia, Debashish; Mohapatra, Himansu Sekhara; Mishra, Akshya Kumar; Khamari, Aishwarya (Journal for Research in Applied Sciences and Biotechnology, 2022)
The menstrual cycle refers to the monthly series of changes a woman's body undergoes to prepare for the potential of conception. The monthly release of an egg from one of the ovaries is known as ovulation. The uterus is also getting ready for pregnancy at the same time as hormonal changes. If the egg is not fertilised, the uterus' lining sheds through the vagina following ovulation. It's now menstruation. There may, however, be additional, more serious menstruation problems. There may be additional issues causing the irregular menstrual cycle if there is excessive or insufficient bleeding, complete lack of a period, or any combination of these. These problems need to be handled properly because they seriously affect female health and fertility. The traditional remedies indigenous women employed to relieve their menstrual discomfort were the focus of this investigation. Unrecognized tribes of the Nuapada District of Odisha are widely known for having a thorough understanding of medicinal plants. A survey was conducted in the Nuapada district's tribal territory from January to February 2021 to learn more about the medicinal plants utilised by tribal women to manage menstrual issues. In their trial to treat abnormal menstrual cycles, they used 10 animals from 8 different groups.